RIVER STATE BORDERS AS A DYNAMIC SPACE OF POLITICAL- GEOGRAPHICAL CONFLICTUALITY - Slyvka, Roman; Zakutynska, Iryna; Hiletskyi, Yosyp; Valuiska, Mariia (Current Problems of Sustainable Development, 2026)
River state borders belong to the most complex and dynamic objects of political-geographical analysis, as they combine the natural variability of river systems with the international legal fixation of state sovereignty. In the modern world, rivers perform not only the function of natural boundaries but also become spaces of political disputes, geopolitical competition, resource conflicts, military-strategic tensions, and transboundary interaction. The article examines the political-geographical specificity of river state borders and the main types of border disputes arising within river systems. Particular attention is devoted to the transformation of rivers from natural landscape elements into politically institutionalized boundaries that simultaneously perform barrier, contact, transport, resource, and security functions. The study analyzes conflicts related to border delimitation within river channels, disputes over islands, changes in riverbeds, the functioning of tripoints and quadripoints, hydraulic engineering projects, navigation regimes, and access to international waterways. Considerable attention is also paid to the influence of erosion, sediment accumulation, floods, avulsion processes, and anthropogenic interventions on the stability of river borders. Examples of river conflicts in Europe, Asia, Africa, and the Americas are considered, including disputes on the Danube, Shatt al-Arab, Amur, Rio Grande, Ganges, and other river systems. These cases demonstrate that river borders often become zones where legal norms, geopolitical interests, historical narratives, and environmental transformations intersect. It is established that modern river borders should not be viewed as static lines, but rather as changing natural and political systems influenced by natural processes, historical treaties, geopolitical interests, climate-related transformations, and engineering interventions. The article emphasizes that the concept of “natural borders,” traditionally widespread in political geography, often contradicts ethnic, historical, economic, and cultural realities, thereby increasing the conflict potential of border regions. The research also highlights the symbolic and geopolitical role of rivers as elements of national identity and spatial imagination. Particular attention is paid to the Ukrainian dimension of the issue, especially the Danube and Dniester directions, the Carpathian river borders, and the growing military-geographical significance of river systems under the conditions of the Russian-Ukrainian war. The destruction of hydraulic infrastructure, increased security risks, and the strategic role of rivers in logistics and defense significantly strengthen the geopolitical importance of river border regions in Eastern Europe. The research emphasizes the importance of river state borders for geopolitical security, transboundary cooperation, international navigation, environmental stability, and the spatial resilience of states in the context of contemporary global transformations.
Keywords: river state borders; political geography; geopolitics; border conflicts; border delimitation; transboundary rivers; international relations